Pengaruh Pola Makan terhadap Status Gizi Ibu Hamil di Wilayah Kerja Puskesmas Lakansai Kabupaten Buton Utara - Wulandari, Indah; Jusmawati, Jusmawati (Universitas Malahayati, 2025)
ABSTRACT In the nutritional status of pregnant women, the balance between nutritional needs and intake plays a very important role. Success in achieving this balance will have a direct impact on the nutritional status of pregnant women. Therefore, it is important for pregnant women to pay attention to a healthy and balanced diet, consume nutritious food and meet their nutritional needs in accordance with the recommendations given by nutritionists or related health workers. Research Objective to determine the influence of eating patterns on the nutritional status of pregnant women in the Lakansai Community Health Center work area in 2024. This research design is cross sectional. This research uses quantitative methods with a cross sectional research design, namely research to study the relationship between the independent variable and the dependent variable by measuring once and at the same time with 30 respondent.. The results of research using the Wilcoxon test and Mann Whitney U test showed that the results of the simultaneous test obtained a significance value of 0.000 which was smaller than α 0.05 so that the conclusion was that the type of food, frequency of eating and number of meals (eating pattern) together ( simultaneous) has a positive effect on LILA. Based on the results of the simultaneous test, a significance value of 0.589 was obtained which was greater than α 0.05, so it was concluded that the type of food, frequency of eating and number of meals (eating pattern) together (simultaneously) had no effect on weight gain. Based on the results of the simultaneous test, a significance value of 0.001 was obtained which was smaller than α 0.05, so it was concluded that the type of food, frequency of eating and number of meals (eating pattern) together (simultaneously) had an effect on Hemoglobin (Hb). Based on the results of research that has been carried out in the Lakansai Community Health Center working area, it can be concluded that eating patterns such as type of food, frequency of eating and number of meals have an effect on the nutritional status of LILA and Hemoglobin (Hb) in pregnant women but have no effect on weight gain. pregnant woman's body. It is hoped that pregnant women will pay attention to their nutritional intake during pregnancy. Keywords: Diet, Nutritional, Status ABSTRAK Dalam status gizi ibu hamil, keseimbangan antara kebutuhan dan masukan nutrisi memainkan peran yang sangat penting. Keberhasilan dalam mencapai keseimbangan tersebut akan berdampak langsung pada status gizi ibu hamil. Oleh karena itu, penting bagi ibu hamil untuk memperhatikan pola makan yang sehat dan seimbang, mengonsumsi makanan bergizi dan mencukupi kebutuhan nutrisinya sesuai dengan anjuran yang diberikan oleh ahli gizi atau tenaga kesehatan yang berkaitan. Tujuan penelitian ini untuk mengetahui Pengaruh Pola Makan Terhadap Status Gizi Ibu Hamil di Wilayah Kerja Puskesmas Lakansai Tahun 2024. Pada penelitian ini menggunakan metode kuantitatif dengan desain penelitian cross sectional yaitu suatu penelitian untuk mempelajari hubungan antara variable independent dengan variable dependen dengan pengukuran sekali dan dalam waktu yang bersamaan dengan 30 responden. Hasil penelitian dengan uji Wilcoxon dan Mann Whitney U Tes didapatkan hasil uji simultan diperoleh nilai signifikansi sebesar 0,000 lebih kecil dari α 0,05 sehingga diperoleh kesimpulan bahwa jenis makanan, frekuensi makan dan jumlah makan (pola makan) secara bersama-sama (simultan) berpengaruh positif terhadap LILA. Berdasarkan hasil uji simultan diperoleh nilai signifikansi sebesar 0,589 lebih besar dari α 0,05 sehingga diperoleh kesimpulan bahwa jenis makanan, frekuensi makan dan jumlah makan (pola makan) secara bersama-sama (simultan) tidak berpengaruh terhadap Penambahan Berat Badan. Berdasarkan hasil uji simultan diperoleh nilai signifikansi sebesar 0,001 lebih kecil dari α 0,05 sehingga diperoleh kesimpulan bahwa jenis makanan, frekuensi makan dan jumlah makan (pola makan) secara bersama-sama (simultan) berpengaruh terhadap Hemoglobin (Hb). Berdasarkan hasil penelitian yang telah di lakukan di wilayah kerja Puskesmas Lakansai dapat ditarik kesimpulan bahwa pola makan seperti jenis makanan, frekuensi makan dan jumlah makan berpengaruh terhadap Status Gizi LILA dan Hemoglobin (Hb) pada ibu hamil namun tidak berpengaruh terhadap Penambahan Berat badan Ibu Hamil. Diharapkan kepada ibu hamil agar memperhatikan asupan nutrisinya selama kehamilan. Kata Kunci: Pola Makan, Status, Gizi